2001
DOI: 10.1191/096032701680350604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-soluble antioxidant from spinach, NAO, on doxorubicin-induced heart injury

Abstract: Doxorubicin (DOX) produces clinically restorative responsesinnumeroushumancancers,butitscardiotoxicity has limited its usefulness. Because reactive oxygen species may affect DOX-induced antitumor activity and cardiotoxicity, weevaluated the prophylactic effect ofspinachnatural antioxidant (NAO) on DOX-induced cardiotoxicity and oxidative stress in female Balb/c mice using histological, electron microscopical and biochemical parameters. Mice were treated with NAO for 7 days prior to and/or for 6 days a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Similarly to many other studies, the DXR-induced myocardial damage reported here was associated with clear myocardial histopathological lesions (myocyte necrosis, degeneration, and inflammatory cell infiltrations). 3,4,5,25 Similar to these studies, significant cytoplasmic vacuolization, myofibrillar disorganization and myofibrillar losses were observed in the histopathological examination of the cardiac tissues in the DXR administered rats compared to the control group, in our study.…”
Section: -21supporting
confidence: 88%
“…Similarly to many other studies, the DXR-induced myocardial damage reported here was associated with clear myocardial histopathological lesions (myocyte necrosis, degeneration, and inflammatory cell infiltrations). 3,4,5,25 Similar to these studies, significant cytoplasmic vacuolization, myofibrillar disorganization and myofibrillar losses were observed in the histopathological examination of the cardiac tissues in the DXR administered rats compared to the control group, in our study.…”
Section: -21supporting
confidence: 88%
“…Its efficiency was tested and proven in a variety of biological systems in vivo and in vitro (Breitbart et al, 2001;Lomnitski et al, 2000aLomnitski et al, , 2000bLomnitski et al, , 2003Nyska et al, 2001Nyska et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The high level of doxorubicin could damage membranes, proteins (e.g., enzymes, structural, and receptors), and DNA that may lead to cardiac dysfunction and apoptosis (Arola et al 2000;Yamaoka et al 2000;Green & Leeuwenburgh 2002;Kumar et al 2002). While the cytoprotective effect of the commonly used antioxidant vitamins (ascorbic acid and vitamin E) remains controversial (Legha et al 1982;Shimpo et al 1991b;Quiles et al 2002) several naturally occurring antioxidants have demonstrated protective role against doxorubicin cardiotoxicity (Chopra et al 1995;Dorr 1996;Kozluca et al 1996;DeAtley et al 1999;Breitbart et al 2001;Abd-Allah et al 2002;Bagchi et al 2003). Therefore, the purpose of this study is to establish a high throughput screening of natural antioxidants for their cardioprotective effect against doxorubicin cardiotoxicity.…”
mentioning
confidence: 99%